RETRACTED: NR2F1-AS1/miR-190a/PHLDB2 Induces the Epithelial–Mesenchymal Transformation Process in Gastric Cancer by Promoting Phosphorylation of AKT3 - Lv, Jinqi; Zhang, Simeng; Liu, Yang; Li, Ce; Guo, Tianshu; Zhang, Shuairan; Li, Zenan; Jiao, Zihan; Sun, Haina; Zhang, Ye; Xu, Ling (Frontiers in Cell and Developmental Biology, 2021)
The median survival time of patients with advanced gastric cancer (GC) who received radiotherapy and chemotherapy was <1 year. Epithelial–mesenchymal transformation (EMT) gives GC cells the ability to invade, which is an essential biological mechanism in the progression of GC. The long non-coding RNA (lncRNA)-based competitive endogenous RNA (ceRNA) system has been shown to play a key role in the GC-related EMT process. Although the AKT pathway is essential for EMT in GC, the relationship between AKT3 subtypes and EMT in GC is unclear. Here, we evaluated the underlying mechanism of ceRNA involving NR2F1-AS1/miR-190a/PHLDB2 in inducing EMT by promoting the expression and phosphorylation of AKT3. The results of bioinformatics analysis showed that the expression of NR2F1-AS1/miR-190a/PHLDB2 in GC was positively associated with the pathological features, staging, poor prognosis, and EMT process. We performed cell transfection, qRT-PCR, western blot, cell viability assay, TUNEL assay, Transwell assay, cell morphology observation, and double luciferase assay to confirm the regulation of NR2F1-AS1/miR-190a/PHLDB2 and its effect on EMT transformation. Finally, GSEA and GO/KEGG enrichment analysis identified that PI3K/AKT pathway was positively correlated to NR2F1-AS1/miR-190a/PHLDB2 expression. AKT3 knockout cells were co-transfected with PHLDB2-OE, and the findings revealed that AKT3 expression and phosphorylation were essential for the PHLDB2-mediated EMT process. Thus, our results showed that NR2F1-AS1/miR-190a/PHLDB2 promoted the phosphorylation of AKT3 to induce EMT in GC cells. This study provides a comprehensive understanding of the underlying mechanism involved in the EMT process as well as the identification of new EMT markers.